"Walking the nitrogen around the ring": Chemical synthesis and spectroscopic characterization of novel 4‐, 5‐, 6‐, and 7‐azaindazole analogs of the synthetic cannabinoid receptor agonist MDMB‐PINACA. Issue 2 (11th November 2021) - Alam, Ryan M.; Keating, John J.
Abstract: Over the past decade, synthetic cannabinoid receptor agonists (SCRAs) have rapidly evolved to encompass a wide range of structurally diverse new psychoactive substances (NPS), including derivatives that incorporate indole, indazole, 7‐azaindole, γ‐carbolinone, or carbazole heterocyclic scaffolds. The introduction of legislative measures seeking to control the availability of NPS on the recreational drug scene has likely contributed to the continued emergence of novel SCRA analogs, which often evade regulatory control. However, the detection and/or identification of azaindazole‐type SCRAs in seized material has not yet been reported (September, 2021). It is plausible that SCRAs bearing a 1, 3‐disubstituted azaindazole scaffold may possess cannabimimetic activity, given their structural similarity with known indole, indazole, and azaindole SCRAs. In view of these antecedents, a set of four novel isomeric 4‐, 5‐, 6‐, and 7‐azaindazole analogs of the known potent indazole SCRA, MDMB‐PINACA, were synthesized using a Pd‐catalyzed aminocarbonylation strategy. The complementary use of ultraviolet (UV) and infrared (IR) spectroscopy, gas chromatography‐mass spectrometry (GC‐MS), high resolution mass spectrometry (HRMS), 1D‐ and 2D‐nuclear magnetic resonance (NMR) spectroscopy, and high performance liquid chromatography (HPLC) has permitted the spectroscopic differentiation, unambiguous structural assignment, and rapid separation of novel isomeric 4‐, 5‐, 6‐, and 7‐azaindazole analogs of the indazole SCRA, MDMB‐PINACA. Abstract : The synthesis, chromatographic and spectroscopic identification of four novel isomeric azaindazole analogs of the synthetic cannabinoid agonist MDMB‐PINACA are presented. Through a combination of techniques, evidence for the unambiguous differentiation between each azaindazole isomer is discussed.